ANALYSIS OF THE MECHANISMS OF THE FORMATION OF THE COMPETITION ON THE REGIONAL LEVEL IN THE CURRENT ECONOMIC CONDITIONS - N. Alekseeva (Publishing House of the State University of Management, 2019)
The content of the main plan of measures, aimed at the development of competition in key sectors of the economy of the Russian Federation has been presented, also the process of gradual transition of certain areas of natural monopolies in the competitive market сondition has been considered. The control indicators, necessary for the consistent implementation of the main directions of development, the level of competition in key areas of the economy have been analyzed in detail. Within the framework of the conducted research, a unique value paradigm of competition has been formulated taking into account the potential impact of various global challenges on it, associated with the processes of the modern economy development.